Hygiene Services in Urban Administration and Management: Issues, Challenges and Realities of Community Health Management - Neaemeka , Abonyi Nichodemus; Dikwa, Sadiq Muhammad (Kashere Journal of Politics and International Relations, 2025)
The issue of open defecation remains a critical public health and governance challenge, particularly in urban areas of low- and middle-income countries. Despite global efforts to improve water, sanitation, and hygiene (WASH) services, many urban centres continue to face significant gaps in access and management. Open defecation is driven by a combination of socio-economic disparities, infrastructural deficits, weak policy implementation, and insufficient institutional coordination. Its implications extend beyond public health to include economic losses, environmental degradation, and social inequities, disproportionately affecting vulnerable populations such as women, children, and marginalised groups. Addressing this challenge requires integrated approaches that strengthen urban governance, promote community participation, and leverage innovative solutions for effective sanitation management. A focus on inclusive and accountable public administration can ensure equitable access to sanitation and hygiene services, contributing to healthier and more sustainable urban environments.